Synthesis and Characterization of Some Ni(II) and Cu(II) Complexes with 2-[(4-Aminophenyl)imino]-1, 2-diphenyl-1-ethanone - K. M. Khalifa; A. M. Hamil; A. Gasem; A. Abdulsalam (E-Journal of Chemistry)
The present work deals with synthesis and characterization of the ligand 2-[(4-aminophnyl)imino]-1,2-diphenyl-1-ethanone and their complexes with Ni(II) and Cu(II) ions. The synthesized ligand and its complexes have been characterized by elemental analysis, infrared, electronic, nuclear magnetic resonance and mass spectra. The metal ligand ratio was found to be 1:1. Square planer geometry for both complexes was suggested.